Acquisition Values and Optimal Financial (In)Flexibility - Hege, Ulrich; Hennessy, Christopher (Review of Financial Studies, 2010)
[This article analyzes optimal financial contracts for an incumbent and potential entrant accounting for prospective asset mergers. Exercising a first-mover advantage, the incumbent increases his share of surplus by issuing public debt that appreciates in the event of merger. Incumbent debt reduces the equilibrium value of entrant assets and thus reduces the return to (likelihood of) entry through two channels: venture capitalists recover less in default and ownership rights provide weaker managerial incentives. High incumbent leverage has a countervailing cost, since the resulting debt overhang prevents ex post efficient mergers if merger surplus is low. Event risk covenants limiting counterparty debt are optimal for the incumbent, further limiting the entrant's share of merger surplus. A poison-put covenant is also optimal for the incumbent, allowing him to extract the same surplus with lower debt face value.]